Production and characterization of Tm3+/Yb3+ codoped pedestal-type PbO-GeO2 waveguides - Assumpcao, T.; Alvarado, M. A.; Alayo, M. I.; Kassab, L. R P [UNESP] (Canadian Science Publishing, Nrc Research Press, 2014)
This work explores the production and characterization of pedestal-type active waveguides based on PbO-GeO2 (PGO) thin films codoped with Tm3+/Yb3+ rare earth ions. Silicon wafers containing around 1.7 mu m of SiO2 thickness were used as substrate, and the pedestal structure was obtained by conventional photolithography and plasma etching in a reactive ion etching reactor. Plasma etching procedures were made in steps to reduce roughness at the laterals and sidewalls of waveguides. Around 0.5 mu m of Tm3+/Yb3+ codoped PGO thin film was obtained by radio frequency magnetron sputtering deposition after etching procedures. Results of scanning electron microscopy confirmed the waveguide pedestal profile. Optical propagation losses around 4, 5, and 20 dB/cm were observed at 1050, 633, and 543 nm, respectively, for waveguide width in the 30-100 mu m range. Near field profiles at these wavelengths and also at 980 nm are also reported and confirmed the multimode coupling behavior. The present results corroborate the possibility of using Tm3+/Yb3+ codoped PGO thin films as active waveguides for photonic applications.